Penerapan Komunikasi Islam dalam Membangun Sistem Kekerabatan Berdasarkan Adat Minagkabau - Ummi Rahmi; M. Rachmat Effendi; Nandang HMZ (UNISBA Press, 2023)
Abstract. The Minangkabau people are known for their adherence to their customs and religion. This is reflected in the popular expression